Penegakkan Hukum dalam Penyelenggaraan Keselamatan dan Keamanan Transportasi Guna Mengurangi Kemacetan dan Kecelakaan Lalu Lintas pada Ruas Tol Trans Jawa - Irman Putra (Institut Teknologi dan Bisnis Semarang, 2024)
Congestion and traffic accidents are the scourge of overall transportation safety and security conditions. Indonesia itself is the 2nd most congested country in Southeast Asia. The aim of this research is to show that in order to optimize the implementation of transportation safety and security through optimizing driving safety management in Indonesia, maximizing the multi-disciplinary approach of policy makers to overcome traffic jams and traffic accidents. Qualitative research uses a descriptive approach to collect data systematically, factually, and quickly according to the description at the time of the research. The results of this research show that there is a need to optimize law enforcement which has an effect on reducing the level of congestion and traffic accidents in order to reduce traffic jams and accidents on the Trans Java toll road in order to strengthen national resilience.